DYNAMICS OF REVICTIMIZATION OF VICTIMS OF SEXUAL VIOLENCE AT THE LAW ENFORCEMENT STAGE: A VICTIMOLOGICAL ANALYSIS - Azzahra Dwi Kanaya; Nazwa Sabrina Azzahra (Papua Law Review, 2026)
This article analyzes the revictimization of sexual violence victims during law enforcement through a victimology perspective. The research uses normative legal methods with a statutory and conceptual approach. The results show that the legal process can lead to further suffering through denial of reports, victim-blaming questions, repetition of statements, disclosure of identities, lack of support, and unsafe encounters with perpetrators. Revictimization occurs when victims are positioned as evidence, rather than as subjects with rights to security, information, participation, and recovery. The success of law enforcement must therefore also be assessed by the system's ability to prevent re-traumatization and maintain the victim's dignity.